Readiness of Jati Larangan Tourism Object and Sengon Park as a Tourist Attraction Effort Recovery Post-Pandemic Economic Activity - Moch. Nur Syamsu; Rakhmat Ashartono; Hesti Purwaningrum; Halim Ahmad (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Jati Larangan and Sengon Park are an example of community innovation in Iroyudan, Guwosari Village, Pajangan District, Bantul Regency, Special Region of Yogyakarta, in a joint effort to create a more prosperous society, through the development of tourism activities. This study uses descriptive research with a qualitative approach, namely research that aims to make a systematic, factual and accurate description of a social or natural phenomenon, by collecting data, then analyzing it with elaborative explanations. The characteristics of tourists in Jati Larangan and Sengon Park are relatively supportive of efforts to restore economic in the tourism activity during the current pandemic, where people's activities and mobility are limited to certain areas around them. The location of Jati Larangan and Sengon Park, which are in a large open area, has resulted in no clash between site conditions and regulations in the government's effort to reduce the rate of transmission of the covid-19 pandemic.